Indonesian Democracy and Islamic Religious Activities in the Age of "New Normal" - Winarni, Leni (Jurnal Politik Indonesia: Indonesian Political Science Review, 2022)
This paper discusses relations of democracy enforcement and religious freedom in the pandemic era of Covid-19 in Indonesia, especially Muslim. In the "new normal" climate, some believe that perhaps one of the best ways to stop the spread is to impose lockdowns. The centralized style of government typically adopts this policy. However, Indonesia does not implement this policy with various considerations. However, on the other hand, when democratic countries such as Indonesia want to impose restrictions on religious activities, this regulation seems a religious freedom limitation. In several cases at the beginning of Covid-19 that hit Indonesia in March, it was often connected to clusters of religious events involving many people. While the policy of restricting worship often drew protests from religious adherents. Against the backdrops of religious politics as the impact of the 2019 democratic party in the Presidential Election, this paper looks at how this phenomenon has become tremendously politicized and has a common thread between those who refused, ignored, and accepted, and even got involved to support government policy. Herein lies the government's importance in managing its citizens' awareness to fight Covid-19 without intending to restrict religious freedom and stopping the politicization of religion.